The Investigative Audit as a Pillar of Accountability: An Integrated Strategy for Detecting Fraud in the Digital Era - Junaidi, Junaidi; Purnama, Yunus Indra; Suparmono, Suparmono; Mahsun, Mohamad (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2025)
Indonesian fraud is a matter of great concern, with significant implications for economic stability and public trust in the government. This study analysed fraud detection and prevention through investigative auditing, internal auditing, forensic accounting, big data analytics, and whistleblowing mechanisms and offered an integrated framework. Investigative auditing is of great value in detecting fraud as it allows in-depth and flexible inquiry without formulaic constraints. Internal audit validates compliance and strengthens internal control procedures, whereas forensic accounting enables a thorough examination of finances to identify potential fraud. Big data analytics, when applied in conjunction with these procedures, facilitates the better detection of fraud through the analysis of sophisticated and bulk data, outlier identification, and the detection of suspicious transaction patterns. An effective whistleblowing scheme also fosters a culture of accountability and transparency, enabling fraud to be identified early. This research discovers that a comprehensive and inclusive model for fraud detection is a key factor in preventing fraud and ultimately leads to enhanced governance and organizational integrity.